2022
DOI: 10.3389/fbioe.2022.842294
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Between Partial Robotic Exoskeletons and Human Gait: A Comprehensive Review on Control Strategies

Abstract: Lower-limb robotic exoskeletons have become powerful tools to assist or rehabilitate the gait of subjects with impaired walking, even when they are designed to act only partially over the locomotor system, as in the case of unilateral or single-joint exoskeletons. These partial exoskeletons require a proper method to synchronize their assistive actions and ensure correct inter-joint coordination with the user’s gait. This review analyzes the state of the art of control strategies to coordinate the assistance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 202 publications
0
6
0
Order By: Relevance
“…This coordination is crucial to avoid instabilities and maximize the benefits of wearing the active device. Mid-level controllers have been previously assessed in a general way for partial and unilateral robotic exoskeletons (Lora-Millan et al, 2022), but without focusing on ankle devices. The most common control strategy to achieve a proper coordination is based on the detection of several gait events that divide the gait into different phases.…”
Section: Mid-level Controlmentioning
confidence: 99%
“…This coordination is crucial to avoid instabilities and maximize the benefits of wearing the active device. Mid-level controllers have been previously assessed in a general way for partial and unilateral robotic exoskeletons (Lora-Millan et al, 2022), but without focusing on ankle devices. The most common control strategy to achieve a proper coordination is based on the detection of several gait events that divide the gait into different phases.…”
Section: Mid-level Controlmentioning
confidence: 99%
“…Their results suggested that healthy subjects are able to embody the robotic assistance, since they reduce muscular activity and, therefore, the energetic cost of walking, increasing their endurance. Most published research works about robotic assistance in hemiparetic patients after stroke are focused on achieving an autonomous and stable gait 27 . Although some authors have reported muscular adaptations, these can not be considered as signs of the device's embodiment.…”
Section: Robotic Exoskeleton Embodiment In Post-stroke Hemiparetic Pa...mentioning
confidence: 99%
“…At this level, the system can have one or more control systems, which can track walking patterns, in which each system contains the necessary kinematic chains for the global system to function correctly when interacting with the human. The mid-level control also coordinates the movement of multiple motorized joints or between multiple devices [26]. It is estimated that the speeds of the nerves in the lower limbs range between 40 and 45 m/s [23]- [25], [27].…”
Section: Human Gait As a Model Of Inspirationmentioning
confidence: 99%